Effect of ultrasound on the concentration of phenolic compounds and antioxidant capacity during the preparation of Berberis vulgaris leaves extracts - Gonzales-Condori, Elvis Gilmar; Garcia-Cari, Juan Carlos; Garcia-Cari, Giovanna; Gonzales-Condori, Jonathan; Alvarez-Gonzales, Rosa (LACCEI, 2024)
The objective of this research was to evaluate the effect of ultrasound application on the concentration of total phenols and antioxidant capacity of ethanolic, hydroalcoholic and aqueous extracts of Berberis vulgaris leaves, extracts were obtained by ultrasound application for 0, 5, 10, 20 and 30 minutes at 40 kHz in an ultrasonic bath. The results indicate that the application of ultrasound affects the extraction process of phenolic compounds in ethanolic and hydroalcoholic extracts, it was also demonstrated that an application longer than 20 minutes leads to a decrease in the concentration of these bioactive compounds. On the other hand, ultrasound positively affects the antioxidant capacity of ethanolic and hydroalcoholic extracts up to 20 minutes; however, in aqueous extracts, ultrasound increases the antioxidant capacity up to 10 minutes of application, since exceeding this time this antioxidant capacity decreases. In conclusion, ultrasound does affect the extraction process of phenolic compounds from Berberis vulgaris leaves and the solvent that favors extraction, guaranteeing a greater antioxidant capacity, is water.